2016
DOI: 10.1523/jneurosci.3881-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in d-Aspartate Oxidase Promoter Methylation Control Extracellular d-Aspartate Levels and Prevent Precocious Cell Death during Brain Aging

Abstract: The endogenous NMDA receptor (NMDAR) agonist D-aspartate occurs transiently in the mammalian brain because it is abundant during embryonic and perinatal phases before drastically decreasing during adulthood. It is well established that postnatal reduction of cerebral D-aspartate levels is due to the concomitant onset of D-aspartate oxidase (DDO) activity, a flavoenzyme that selectively degrades bicarboxylic D-amino acids. In the present work, we show that D-aspartate content in the mouse brain drastically decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 63 publications
9
88
0
Order By: Relevance
“…We used DDO as a model gene because, during development, this gene undergoes methylation in lung and gut (this manuscript) and demethylation in brain. 23 Moreover, the chosen system allowed us to study these processes in a natural context (tissues rather that cell lines), and to follow methylation changes occurring during development, thus avoiding any artifacts due to the action of drugs. Finally, the analyzed DDO methylation/demethylation processes are relevant for gene function, and thus may be a consequence of a deterministic phenomenon, since they are accompanied by gene activation (brain) 23 or gene repression (gut and lung).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used DDO as a model gene because, during development, this gene undergoes methylation in lung and gut (this manuscript) and demethylation in brain. 23 Moreover, the chosen system allowed us to study these processes in a natural context (tissues rather that cell lines), and to follow methylation changes occurring during development, thus avoiding any artifacts due to the action of drugs. Finally, the analyzed DDO methylation/demethylation processes are relevant for gene function, and thus may be a consequence of a deterministic phenomenon, since they are accompanied by gene activation (brain) 23 or gene repression (gut and lung).…”
Section: Discussionmentioning
confidence: 99%
“…Since we recently determined that a specific DDO promoter region undergoes demethylation in the brain during development, 23 here we checked whether the same region exhibits the opposite behavior in other tissues. DNA methylation was assessed through a strategy based on the locus-specific amplification of bisulfite-treated genomic DNA.…”
Section: Choice Of Biological Systemmentioning
confidence: 99%
“…Although D-aspartate is abundant in the brains of rodents and humans during development, levels of D-aspartate are extremely decreased at postnatal stages and this reduction remains throughout adulthood [16, 67, 68, 71, 87, 88]. In contrast, DDO activity and its mRNA are exceedingly low at postnatal stages and increase after birth in rodents [88, 89]. Moreover, it has been shown that D-aspartate levels were significantly elevated in the CNS of Ddo knockout mice [88, 9093].…”
Section: D-aspartatementioning
confidence: 99%
“…In contrast, DDO activity and its mRNA are exceedingly low at postnatal stages and increase after birth in rodents [88, 89]. Moreover, it has been shown that D-aspartate levels were significantly elevated in the CNS of Ddo knockout mice [88, 9093]. In addition, D-aspartate is found exclusively in the neurons of rats [67].…”
Section: D-aspartatementioning
confidence: 99%
See 1 more Smart Citation